Strategi Guru Fiqih Dalam Meningkatkan Praktik Shalat Berjamaah Pada Siswa Madrasah Aliyah - Pradani*, Adesta Dellya; Abidin, Zaenal (Universitas Syiah Kuala, 2023)
The purpose of this observation is to know what are the strategies used by fiqh teachers as well as factor supporters and obstacles in enhancing practical experience Salat congregates with students at MAN Wonogiri. The research of this study is a field research (field research) using qualitative methods with a descriptive approach. This observation was carried out at MAN Wonogiri with interview and observation data collection techniques to obtain the desired data. To determine the validity of the data using strategy and method triangulation. Data were analysed using an interactive model with the stages of data collection, data condensation, data presentation, verification and drawing conclusions. The results of observing the teacher's strategy jurisprudence to enhance practical experience Salat in congregation with students at MAN Wonogiri with the lecture method and the advice method. Supporting factors, namely: encouraging students to pray in congregation is awareness of the virtues of praying in congregation, self-awareness as a devout Muslim of their obligations, the existence of a mosque, a place for ablution, and toilets which are the main facilities. obstacle factor in terms of namely; there are students performing congregational prayers just wanting to get additional grades or are afraid of punishment or sanctions., lack of attention from parents.